Respuesta :
Answer:
Step-by-step explanation:
f- 2 = 6(d-2)
f - 2 = 6d - 12
f = 6d - 12 + 2
f = 6d - 10 .................................... eq 1
f + 18 = 2(d+18)
f + 18 = 2d + 36
f= 2d + 36 - 18
f = d + 18 .......................................... eq 2
eq1=eq2
6d - 10 = 2d + 18
6d - 2d = 18 + 10
4d = 28
d = 28/4
d = 7 yrs is the daughter's age
Take eq 1
f = 6(7) - 10
f = 42 - 10
f = 32 yrs is Father's age
The present age of the man is 32 and the present age of his daughter is 7.
Two years ago a man was six times as old as his daughter.
In 18 years, the man will be twice as old as his daughter.
We will make two equations using these two statements.
What is substitution method?
The substitution method is used to solve a system of equations. In this method, we first solve one equation for one variable and substitute
the value of this variable in the other equation.
Let the present age of the man be X and the present age of his daughter be Y.
Two years ago means we need to subtract 2 from the present age.
We have,
X - 2 = 6 ( Y - 2 )
X - 2 = 6Y - 12...........(1)
In 18 years means we need to add 18 to their present age.
X + 18 = 2 ( Y + 18 )
X + 18 = 2Y + 36.........(2)
Solving equations (1) and (2) using the substitution method.
From (1) we have,
X = 6Y - 12 + 2
X = 6Y - 10.........(3) putting this in (2)
6y - 10 + 18 = 2Y + 36
6Y - 2Y = 36 - 8
4Y = 28
Y = 7 Putting in (3)
X = 6(7) - 10
X = 42 - 10
X = 32
We have X = 32 and Y = 7.
The present age of the man is 32 and the present age of his daughter is 7.
Learn more about age problems here:
https://brainly.com/question/15361201
#SPJ5